Геоэлектрическая модель земной коры и верхней мантии вдоль профиля ГСЗ Новоазовск-Титовка - Логвинов, И.М.; Тарасов, В.Н. (Геофизический журнал, 2015)
Наведено результати двовимірної інверсії магнітотелуричних даних уздовж профілю ГСЗ Новоазовськ-Титовка. В межах Донбасу виділено два об'єкта зниженого опору (які зумовлюють Донбаську аномалію провідності). Один об'єкт залягає в осадових породах (в інтервалі глибин 1-10 км) у південній частині регіону, інший - в центральній частині (в інтервалі глибин 1-18 км) і проникає в консолідовану кору. Загальна інтегральна провідність об'єктів порядку 3·10⁸ См·м. Просторово об'єкти добре корелюють з вугленосними породами карбону. The results of interpretation of magnetotelluric data, focused on the along DSS profile Novoazovsk-Titovka by the two-dimensional inversion have been presented. On the territory of Donbass allocated 2 properties of low resistance (conductivity anomaly causing Donbass) occurring: in the southern part of the sediment (at a depth of 1-10 km), in the central part (at a depth of 1-18 km) in sedimentary rocks and penetrating into consolidated crust. Total cumulative integral conductivity objects about 3 · 108 S · m. The most reliable object spatially correlates with the coal-bearing rocks of the Carboniferous.